Zabezpieczenie wypadkowe a reforma ubezpieczeń społecznych - Jędrasik- Jankowska, Inetta (Wydział Prawa i Administracji UAM, 1995)
The paper presents an opinion in the discussion concerning a draft proposal of the Ministry of Labour and Social Policies concerning the reforms in the social security system. A special attention has been given to accident and injury at work insurance, injuries and injury benefits as well as pensions for retired workers unable to work after an accident at work. The author postulates restoration of the recourse in relation to the insured enterprises, including private ones. In the context of the existing legislative regulations in Poland, the draft proposal referred to in the paper received a critical review. Although, generally speaking, the proposed division of the social fund into three separate funds (pension fund, sickness/disability fund and accident fund), is justified, in the opinion of the author of the paper two of those funds and benefits from those funds will overlap. Both the sickness/disability fund and the accident fund will be used to source eg. benefits for the disabled and rehabilitation benefits. Therefore such a division will not be cost-effective.
Accident insurance and the reform of social security system